Profile Of Attendees in The Anti-Retroviral Therapy Centre in Medical College in Jabalpur, India - Arya Rajendra Singh; Prasad Pankaj (Medsci Publications, 2012)
Background: Acquired Immune Deficiency Syndrome (AIDS) has piled enormous tension all over the world in recent times due to its diverting phenomenon. Recent estimates of more than 2.5 million infected HIV cases in India contribute largest number in the world. Objective: To assess the socio-demographic profile of HIV /AIDS patients attending the ART centre in Medical College; to study the trend of the mode of transmission among HIV/AIDS patient in the ART centre and to assess the risk behavior pattern among HIV/ AIDS patient in the ART center. Material and Methods: During the study period of August 2008 to July 2009, data was collected by every alternate day visit in order to take at least 50% of ART attendees in our study. Interview was taken by using predesigned, pretested questionnaire. Result: Out of 250 cases observed 169 were males and 81 were females. Maximum 98% of ART attendees had sex with heterosexual partners reveals that these people acquired this disease through heterosexual mode & 1.6% from homosexual mode and 0.4% attendees got infected by both heterosexual & homosexual modes. Conclusion: People have begun using ART center services, which reflect a change in their attitude toward HIV. The study provides us a clue to formulate an effective approach to educate people as well as the health personnel who are though of as one of the sources of discrimination.